Análise tecnológica sobre os aspectos ambientais de empreendimentos hoteleiros da Praia de Ponta Negra Natal/RN: um modelo de sistema de gestão ambiental - Nicodemo, Leonardo Pivôtto (2008)
The present work aimed the elaboration of an environmental study focused on the hotel sector in order to present an analysis of the environmental aspects of Ponta Negra Beach, in Natal, RN, Brazil and also the aspects of the small and medium hotels existing in this area. By means of this work, it is possible to elaborate a model of a simplified System of Environmental Management which can attend to the exigencies required by NBR ISO 14001: 2004, as well as to present economical viability and possibility to be implemented in a way that hotels may converge to the sustainable environmental development of the tourism in Ponta Negra Beach. The research methodology presents itself divided into three items: execution of the environmental characterization of Ponta Negra Beach, by way of technical visits and interpretation of satellite images and cartograms of the main environmental characteristics of the region; execution of the work already made concerning the development, application and interpretation of the evaluation of the environmental aspects of each hotel, considering the hotels and the period of data collection, these used in evaluation, research instrument and a description of the procedure utilized for the analysis of the collected data and the utilized methodology for the elaboration of a model of a simplified System of Environmental Management. In a general way, it has been concluded that the practices executed by hotels in Ponta Negra Beach are impact-like and harmful to the environment. The simple implementation of analysis procedures and control of the environmental aspects could suggestively contribute to the reduction of environmental impacts promoted by the hotel section at this beach and in the nearby areas. It had been noticed that the study contributed to the sensitization of managers concerning the environmental problems since, in many other times, the detected problem was, in fact, the non-acquaintance about the environmental aspects and impacts from those hotels administrators, because of the lack of surveys and studies about the theme. It had also been noticed the arousing of a possible environmental attitude from some managers